Antecedents And Consequences Of Work Engagement: A Study Among Engineers In The Electrical And Electronics Sector In Penang - Mat Saad, Abu Bakri (Universiti Sains Malaysia, 2009)
This research studied the antecedents and consequences of work engagement among engineers in electrical and electronics manufacturing firms in Penang. The antecedents for work engagement were job demand and job resources. Job demand variables were quantitative demand, emotional demand and cognitive demand. Whereas job resources variables were job autonomy, perceived supervisory support and perceived organization support, distributive justice and procedural justice. The consequences of work engagement consist of work related outcomes, career satisfaction, turnover intention, organization commitment and task performance.